SISTEM INFORMASI PEMESANAN MENU BERBASIS QR CODE PADA COFFE SHOP UMCO MENGGUNAKAN VISUAL BASIC STUDIO 2010 - DWI SAPUTRA, RIYAN; JOELDA, SETIO; AMELLYA, SRI; AGUSTINA AMIN, SERLY (JURNAL DATA SAINS DAN TEKNOLOGI INFORMASI (DASTIS), 2025)
The development of information technology has driven innovations in various sectors, including the culinary industry. Coffee Shop UM.Co faces challenges in improving the efficiency of the ordering process and customer service. Therefore, this study aims to develop a QR Code-based Menu Ordering Information System using Visual Basic Studio 2010. This system allows customers to scan the QR Code on the table using their mobile devices, then select and order the menu directly without the need to wait for a server. The system development method uses the Waterfall model, which includes stages of analysis, design, implementation, and testing. The developed system includes key features such as digital ordering, menu management, and transaction reporting to support the operational efficiency of Coffee Shop UM.Co. The test results show that this system is capable of improving the speed and accuracy of orders, reducing queues, and providing a better customer experience.